Menuju Tata Kelola Bumdes Yang Baik Melalui Digitalisasi Dan Konsolidasi Laporan Keuangan - Aprillianto, Bayu; Maharani, Bunga; Sayekti, Yosefa; Irmadariyani, Ririn; Indah Purnamawati, Indah; Sulistiyo, Agung Budi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Indonesian Government encourages the increasing of village economic through Village Owned Enterprise (BUMDes). Good governance of BUMDes has to have accountability and transparency. Condition of financial reporting of BUMDes in Tengger Mountain and Pandalungan society is still manual, excel-based, moreover having unpublished-financial reporting. Financial reporting form is still only report of cash receipts and contests and not accrual base. Hence, need to digitalize consolidated financial reporting based on Microsoft Access within business units. Keywords: BUMDes, Consolidation, Digitalzation, Financial Report.